Crystal structure assessment of Ge-Sb-Te nanowires. (July 2017) - Lazzarini, Laura; Rotunno, Enzo
Abstract: 1D semiconductor nanostructures, owing to their low dimensionality, exhibit novel properties that find application in many device fields. In addition, they can present crystal structures different from their common ones, due to the size effect or to their growth mechanism. Ge-Sb-Te compounds are the most widely employed materials for phase-change memory devices that must be downscaled to nanosize to reduce the power consumption. This imposes a better understanding of the phase transition mechanism, as well as a deeper knowledge of the structure of the phases involved in the transition. In this work, we present how the TEM techniques, in particular high resolution STEM-HAADF combined with proper simulations, allow identifying and assessing the crystal structure of uncommon/unforeseen polymorphs in phase-change Ge-Sb-Te nanowires.